Examining the Relationships Among Parental Overprotection, Military Life Adjustment, Social Anxiety, and Collective Efficacy - Bark, Kyounghee; Ha, Jung Hee; Jue, Juliet (Frontiers in Psychology, 2021)
The purpose of this study was to verify the relationships among parental overprotection (PO), military life adjustment (MLA), social anxiety, and collective efficacy (CE). There have been studies examining the influence of each of these variables in isolation, but no study has examined these variables simultaneously. Two hundred and thirty-one male conscript soldiers participated in the study. Results indicated that all four variables were correlated with one another. Through hierarchical regression analysis, we determined that social anxiety fully mediated the relationship between PO and MLA. Furthermore, we found that CE moderated the relationship between PO and social anxiety. Finally, we confirmed the moderated mediation effect of CE in our proposed model. We discuss the implications and limitations of this model.